Care for children after burn injury - Kripner, J; Broz, L; Königová, R (Acta chirurgiae plasticae, 2004)
Authors are summing up basic approach in the treatment of severe burn injury in children. Thorough evaluation of severity of the injury is essential and determines further therapy. In this phase connection between care prior to hospitalization and in hospital is important. During the course of therapy in hospital, interdisciplinary teamwork is essential for the solution of various complications after burn injury. Important part of the care is cooperation with family of the child.
Keywords: Child; Burns; Intensive Care Units; Humans; popálení; Česká republika; jednotky intenzivní péče; lidé; dítě; Czech Republic